Optical properties of zinc borotellurite glass systems doped with dysprosium oxide and dysprosium oxide nanoparticles - Mohd Nor, Ami Hazlin (2017)
Two series of zinc borotellurite glass systems doped with dysprosium oxide and dysprosium oxide nanoparticles with chemical formula of {[(TeO2)0.7(B2O3)0.3]0.7(ZnO) 0.3}1-x (Dy2O3)x (where x = 0.01, 0.02, 0.03, 0.04, and 0.05 molar fraction) were fabricated by using melt-quenching method. The physical, structural and optical properties of the zinc borotellurite glass systems at various concentration of dopants have been studied. The amorphous nature of the two glass systems was confirmed by using XRD analysis. The infrared spectra obtained from the FTIR spectroscopy for both series of the glasses revealed the existence of five obvious bands which were assigned to the BO3, BO4, TeO3 and TeO4 vibrational groups. The presence of the Dy2O3 NP in the zinc borotellurite glass network was proven by TEM image. The values of the density of zinc borotellurite glass doped with Dy2O3 and Dy2O3 NP were found to increase from 4.4181 to 4.94941 g/cm3 and from 4.4210 to 5.0081 g/cm3 respectively with the addition of dopants. The decrement of the molar volumes of both glasses follow the relationship between the density and the molar volume which supposed to be inversely proportional to each other. For the zinc borotellurite glass systems doped with Dy2O3, the indirect and direct optical band gaps were found to increase from 3.0000 to 3.0430 eV and 3.0800 to 3.1150 eV, respectively as the concentration of Dy2O3 increased. On the other hand, the direct and indirect optical band gaps for the zinc borotellurite glass systems doped with Dy2O3 NP were found to decrease in the range of 3.2880 to 3.3110 eV and 3.0015 to 3.0309 eV as the concentration of Dy2O3 NP was increased. The values of Urbach energy for both glass series were inversely proportional to the optical band gaps of the glass samples. The Urbach energy of Dy2O3 doped glass systems was observed in the range of 0.3389 to 0.3411 eV while the Urbach energy for Dy2O3 NP doped glass systems was in between 0.4010 to 0.4219 eV. As the concentration of the Dy2O3 increased, the refractive index of Dy2O3 doped zinc borotellurite glass was found to decrease from 2.0410 to 2.0310, which in turn reduced the electronic polarizability, oxide ion polarizability and optical basicity of the glass systems. As in case of Dy2O3 NP doped zinc borotellurite glass, the refractive index of the glass systems was found to increase from 2.0340 to 2.0410 as the concentration of Dy2O3 NP increased. The values of electronic polarizability, oxide ion polarizability and optical basicity were found to be inversely proportional to the refractive index of the zinc borotellurite glass systems doped with Dy2O3 NP. The increment in the values of the metallization criterion of the first series of the glass systems which were found in the range of 0.4866 to 0.4898 indicates that the materials were prone to act as an insulator. In contrast, the slight decrement of the metallization criterion of the second series of the glass systems from 0.4944 to 0.4934 suggests that the glass samples are metallizing. From the emission spectra of both series of glass system which were obtained from Luminescence spectrometer, two transition bands were observed which represent the transitions from 4F9/2 to 6H15/2 and 6H13/2. In addition, the x and y CIE chromaticity coordinates which were determined from the emission spectra and were found to be located in the region of white light spectrum. In this research, it is also proven that the values of the correlated colour temperature obtained for both glass systems fall in the neutral white light region.